Nutritional value of sorghum for poultry feed in West Africa - Issa, Salissou (Kansas State University, 2009)
A total of 2,840 1-d-old broiler chicks and 450 1-d-old layer chicks were used in three experiments to determine the nutritional value of corn- and sorghum-based diets in poultry reared in West Africa. In the broiler experiments, birds fed corn had greater average daily gain (P < 0.001) with similar carcass weight and yield for birds fed corn- vs sorghum-based diets (P > 0.18). Particle size treatments did not affect growth performance or carcass characteristics (P > 0.20). In the layer experiment, birds fed sorghum had greater body weight at d 126 (P < 0.001), started laying earlier (P < 0.01), ate more feed (P < 0.01), and produced more eggs (P < 0.01) than birds fed the corn-based diet. However, there was no difference in average egg weight among birds fed corn vs sorghum (P > 0.85). In conclusion, sorghums produced in West Africa are a good alternative to corn when fed to broiler chicks and laying hens.
Keywords: Corn; Sorghum; Particle-size; Broilers; Layers; Agriculture, Animal Culture and Nutrition (0475)